Pengaruh Pendekatan Pembelajaran Scientific Berbantukan Simulasi Phet terhadap Hasil Belajar Tematik Kelas IV - Indah Mustiksari; Naniek Kusumawati H; Heny Kusuma Widyaningrum (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the effect of Phet Simulation-Assisted Scientific Approach on Thematic Learning Outcomes. Theme 8 sub-theme 1 learning 1 semester 2 Class IV SDN Pilangbango Madiun. This research uses quantitative research using quasi-experimental method, the design in this research is Non-Equivelent Control Design because this research involves two classes in the sample. The control class uses conventional learning, while the experimental class uses a scientific approach assisted by phet. This study uses documentation in the form of observation sheets, and test results as data collection instruments. The data analysis technique used is validity test, reliability test, level of difficulty, difference power test, t test.